Expression of ob gene coding the production of the hormone leptin in hepatocytes of liver with steatosis - Bartek, J; Bartos, J; Galuska, J; Galusková, D; Stejskal, D; Ivo, K; Ehrmann, J; Ehrman, J; Chlup, R (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2001)
Leptin is a circulating pleiotropic hormone that play an important role in appetite control, fat metabolism, regulation of body weight, fetus growth, growth and aging of adults and hematopoiesis. It is expressed abundantly and specifically in the adipose tissue. A liver cell with developed steatosis represents a cell metabolism similar to metabolism of cells of adipose tissue. Analyses of serum leptin and free leptin receptor in the serum of patients with steatosis showed significant variations from reference limits of normal values. However in liver tissue with verified steatosis detection of mRNA gene for leptin was not proven. Such expression of ob gene for leptin was not found even in the liver tissue without steatosis. With respect to the absence of ob gene expression, the direct effect of ob gene expression on other parameters of leptin metabolism could not be evaluated. The RT-PCR method with verified specificity and satisfying sensitivity was developed. The results obtained from analysis of serum leptin and free leptin receptor in the serum are presented and evaluated. The used methods were verified and reference limits for Czech population were defined in dependence on age and other clinical parameters.
Keywords: hepatocyty; Female; Fatty Liver; polymerázová řetězová reakce; Polymerase Chain Reaction; ženské pohlaví; Leptin; lidé; ztučnělá játra; messenger RNA; Hepatocytes; RNA, Messenger; leptin; Male; exprese genu; lidé středního věku; mužské pohlaví; Middle Aged; Gene Expression; Humans